Effects of Home-Based Pulmonary Rehabilitation with a Metronome-Guided Walking Pace in Chronic Obstructive Pulmonary Disease - Lee, Sung-soon; Kim, Changhwan; Jin, Young-Soo; Oh, Yeon-Mok; Lee, Sang-Do; Yang, Yun Jun; Park, Yong Bum (Journal of Korean medical science, 2013)
Despite documented efficacy and recommendations, pulmonary rehabilitation (PR) in chronic obstructive pulmonary disease (COPD) has been underutilized. Home-based PR was proposed as an alternative, but there were limited data. The adequate exercise intensity was also a crucial issue. The aim of this study was to investigate the effects of home-based PR with a metronome-guided walking pace on functional exercise capacity and health-related quality of life (HRQOL) in COPD. The subjects participated in a 12-week home-based PR program. Exercise intensity was initially determined by cardiopulmonary exercise test, and was readjusted (the interval of metronome beeps was reset) according to submaximal endurance test. Six-minute walk test, pulmonary function test, cardiopulmonary exercise test, and St. George's Respiratory Questionnaire (SGRQ) were done before and after the 12-week program, and at 6 months after completion of rehabilitation. Thirty-three patients participated in the program. Six-minute walking distance was significantly increased (48.8 m; P = 0.017) and the SGRQ score was also improved (-15; P < 0.001) over the six-month follow-up period after rehabilitation. There were no significant differences in pulmonary function and peak exercise parameters. We developed an effective home-based PR program with a metronome-guided walking pace for COPD patients. This rehabilitation program may improve functional exercise capacity and HRQOL.